PERAN KEPALA DESA TERHADAP PERILAKU MENYIMPANG DIKALANGAN PEMUDA DESA KOLELET KECAMATAN PICUNG KABUPATEN PANDEGLANG - Enas Munajat; E. Nita Prianti; Alamsyah Basri; Rini Kusrini (Bajang Institute, 2022)
This research was conducted in Kolelet village, Picung sub-district, Pandeglang district with the aim of 1) To determine the role of the village head towards deviant behavior among the youth of Kolelet Village, Picung District, Pandeglang Regency. 2. To find out what efforts are being made by the community towards behavioral deviations among the youth of Kolelet Village, Picung District, Pandeglang Regency. The method used is a qualitative method with data collection through observation, interviews and documentation techniques. The analysis used is by using triangulation with data reduction techniques, data display and data verification. The results obtained in this study are that the role of the head of the Kolelet village, Picung sub-district, Pandeglang district is quite good. Based on the results of observations and interviews, it shows that the village head has carried out his duties in terms of minimizing deviations in youth behavior by taking part and cooperating in participating and providing appeals. to always be vigilant to its citizens in maintaining self-security, urge to behave positively, provide examples of positive attitudes and behavior, appreciate the work of youth, provide sanctions according to deviations committed by the perpetrators